EFEKTIVITAS DOSIS MODIFIKASI SORAFENIB TERHADAP KESINTASAN PASIEN KARSINOMA SEL HATI STADIUM LANJUT: SUATU LAPORAN KASUS BERBASIS BUKTI - Roland Helmizar (Nusantara Hasana Journal, 2023)
Background: Sorafenib is a multi-tyrosine kinase inhibitor that has been shown to improve survival in patients with advanced stage hepatocellular carcinoma (HCC). Based on the search to date, there are quite number of studies evaluating the effectiveness and safety of sorafenib dose modification on the survival of patients with advanced HCC; however, the previous studies have showed varying results. Method: A comprehensive literature search was conducted using three electronic databases: PubMed, Cochrane and EBSCohost. Meta-analyses, randomized controlled trials (RCTs), and cohort studies were selected based on inclusion and exclusion criteria. The quality of selected studies was evaluated using critical appraisal tools developed by the Center for Evidence-Based Medicine. Results: Three cohort studies were included in this report. In general, of the three studies that have been reviewed, show that reducing the dose of sorafenib from 800 mg/day to 400 mg/day does not affect the mean or median survival of patients with advanced HCC. Conclusion: Administration of sorafenib with initial dose of 400 mg/day or decreasing the dose from 800 mg/day to 400 mg/day has good tolerance, with not significantly difference on overall survival. But more evidence is required before they can be widely recommended in clinical practice for this indication.